2008
DOI: 10.1183/09031936.00097707
|View full text |Cite
|
Sign up to set email alerts
|

Wood smoke exposure induces a pulmonary and systemic inflammatory response in firefighters

Abstract: Epidemiological studies report an association between exposure to biomass smoke and cardiopulmonary morbidity. The mechanisms for this association are unclear. The aim of the present study was to characterise the acute pulmonary and systemic inflammatory effects of exposure to forest fire smoke.Seasonal forest firefighters (n552) were recruited before and/or after a day of fire-fighting. Exposure was assessed by questionnaires and measurement of carbon monoxide levels (used to estimate respirable particulate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
172
3
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(190 citation statements)
references
References 55 publications
4
172
3
7
Order By: Relevance
“…The overall prevalence of expectoration in the present study was lower than that found by another group of authors, (3) who reported expectoration in 36% of charcoal production workers, as well as being lower than the 28.9% found in the study involving wildland firefighters and the 27.1% . (7) In another study, (9) chronic expectoration was reported in 27.1% of the individuals exposed to the dust in silos, a prevalence that was also higher than that found in the present study.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…The overall prevalence of expectoration in the present study was lower than that found by another group of authors, (3) who reported expectoration in 36% of charcoal production workers, as well as being lower than the 28.9% found in the study involving wildland firefighters and the 27.1% . (7) In another study, (9) chronic expectoration was reported in 27.1% of the individuals exposed to the dust in silos, a prevalence that was also higher than that found in the present study.…”
Section: Discussioncontrasting
confidence: 51%
“…(11) In the present study, charcoal workers who lived within 200 m of the kilns were more likely to present nasal obstruction, which was reported by 22 (32.83%) of the 67 workers interviewed. This prevalence is higher than the 20% found in the study involving wildland firefighters in Canada (7) but lower than the 42.7% found in the study involving pig farmers in the city of Braço do Norte. (6) In the present study, allergic rhinitis was observed in 6 (9%) of the 67 workers investigated, and occupational rhinitis was observed in 14 (20.9%).…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…The short term effects of exposure to high levels of air pollution are likely to cause inflammatory responses in the lung and release of cytokines with local and systemic consequences [24,77]. Acute effects of PM exposure have also been shown to increase plasma viscosity [25,78].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological evidence includes work by Swiston et al (2008) who observed lung inflammation and an increased presence of white blood cells and band cells (markers of systemic inflammation) in firefighters that were acutely exposed to wood smoke the previous day. Cook stove interventions that led to ~60% reductions in daily wood smoke exposures for Guatemalan women, have also been associated with reduced blood pressure and cardiac stress (ST-depression) (McCracken et al, 2007;McCracken et al, 2011).…”
Section: Biomass Smokementioning
confidence: 99%